The threat of monitoring job search: A discontinuity design - Bart Cockx; Muriel Dejemeppe (Institute for the Study of Labor (IZA), 2010)
Since July 2004 the job search effort of long-term unemployed benefit claimants is monitored in Belgium. We exploit the discontinuity in the treatment assignment at the age of 30 to evaluate the effect of a notification sent at least 8 months before job search is verified. The threat of monitoring increases transitions to employment, but of lower quality. In the less prosperous region, Wallonia, the impact is smaller, despite of the presence of specific counseling for the notified workers, and more heterogeneous. Moreover, in this region, the threat induces women to substitute sickness for unemployment benefits.
Keywords: J64; J65; J68; H43; 330; evaluation; monitoring job-search; threat effect; regression-discontinuity; grouped data